Transcriptomic, Metabolomic, and Physiological Analyses Reveal That the Culture Temperatures Modulate the Cryotolerance and Embryogenicity of Developing Somatic Embryos in Picea glauca - Cui, Ying; Gao, Ying; Zhao, Ruirui; Zhao, Jian; Li, Yixuan; Qi, Shuaizheng; Zhang, Jinfeng; Kong, Lisheng (Frontiers in Plant Science, 2021)
In vitro culture of somatic embryos (SEs) is an ideal system to study environmental effects on embryo development in plants. Developing SEs of Picea glauca obtained their cryo-tolerance of 100% tissue survival when cultured on maturation medium at either 23ºC for four wks or 4ºC for ten wks. However, only the embryos underwent 4ºC acclimation remained high embryogenicity, i.e. 91.7% on cryovials or 29.3% on plant tissue. Analysis of differentially expressed genes revealed that both 23ºC and 4ºC treatments led to drastic changes in gene expression, i.e. 21,621 and 14,906 genes respectively, and the general increase in many oligosaccharides and flavonoids, in addition to content change of proline (1.9 and 2.3 fold at 23 or 4 ºC) and gallic acid (6,963 and 22,053 fold). There were 249 significantly different metabolites between the samples of 23ºC and 4ºC treatments and the change trend of sorbitol, fatty acids, monosaccharides differed between these samples. During 4 ºC acclimation, the metabolites of arginine biosynthesis pathway increased between 2.4 fold and 8.1 fold and the expression of antioxidant genes was up-regulated significantly. At 4 ºC, the up-regulated genes were for germ-like proteins, instead of seed storage proteins at 23 ºC. Concentrations of abscisic acid and jasmonic acid increased up to 2.0 and 1.5 fold respectively in the cold-acclimated embryos. After 10 wks at 4 ºC, the embryos stayed at pre-cotyledonary stage with 17.1% less DNA methylation and fewer storage substances than those at 23ºC for four weeks, which developed cotyledons. This research provides new insights into mechanisms underlying the response of SEs to different culture temperatures and benefits method development for germplasm conservation in conifers.